2001
DOI: 10.1016/s0924-9338(01)00581-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of compliance with neuroleptic medication among inpatients with schizophrenia: a discriminant function analysis

Abstract: These data emphasise the complexity of factors that influence whether a person adheres to his medication regimen. Furthermore, they suggest that these factors may vary within the same person over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 14 publications
5
62
1
5
Order By: Relevance
“…This analysis was performed by univariate analyses of variance using a critical value of ␣=.008 in light of the comparison of the total score and 5 indexes. We used a multivariate discriminant function analysis 57 to define the components of the RBANS that provided the most significant contribution to the association with the total score. We also determined the Pearson correlation coefficient between the quantitative level of antibodies, expressed as the ratio calculated as described above, and the RBANS total score using a critical value of ␣=.008.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis was performed by univariate analyses of variance using a critical value of ␣=.008 in light of the comparison of the total score and 5 indexes. We used a multivariate discriminant function analysis 57 to define the components of the RBANS that provided the most significant contribution to the association with the total score. We also determined the Pearson correlation coefficient between the quantitative level of antibodies, expressed as the ratio calculated as described above, and the RBANS total score using a critical value of ␣=.008.…”
Section: Methodsmentioning
confidence: 99%
“…Studies carried out in recent years have evaluated the complexity of pharmacotherapy in a wide array of diseases, such as epilepsy 5 , schizophrenia 11 , hypertension 12 , type-2 diabetes 13 , HIV/AIDS 3,6 and specific population groups such as the elderly [14][15][16] , polymedicated patients 1 and renal transplanted patients 17 . Some of these studies have demonstrated that the critical points of the complexity of pharmacotherapy can vary depending on the patients' characteristics, such as, for instance, the use of 12 or more doses of medications per day in elderly patients 15 or the dietary restrictions imposed by the administration of the medications in HIV-positive patients 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Our operational definitions of mild, moderate, and severe nonadherence are presented in Table 3. This adherence categorization system builds on our previous investigation (24) as well as that of Donohoe et al (25).…”
Section: Nonadherencementioning
confidence: 88%